PERTANGGUNGJAWABAN PIDANA DIREKTUR PERSEROAN TERBATAS DALAM TINDAK PIDANA KORUPSI PROYEK TERBATAS PEMBANGUNAN RUMAH SAKIT (STUDI PUTUSAN NO.15 /PID.SUS-TPK/2018/PN.MDN) - Marthin Simangungsong; Herlina Manullang; Tulus R.G Purba (Magister Hukum Universitas HKBP Nommensen, 2021)
The existence of corporations in the Criminal Code provisions that currently apply has not clearly stipulated corporations as perpetrators of crime because only Article 59 of the Criminal Code still regulates corporate provisions. However, the provisions of regulations outside the Criminal Code have clearly regulated the existence of corporations as legal subjects such as Law Number 40 of 2007 concerning Limited Liability Companies. Corporate criminal crime in its development has been widespread in people's lives, this can be done by the management of the corporation itself. The form of corporation in its development is in the form of legal entity and non-legal entity, one of which is a legal entity is a Limited Liability Company, in Article 82 of the Company Law Director is the management of the company, the Director represents the Limited Liability Company in and out of Article 82 of the Company Law. As for the problem in this research is how the criminal responsibility of the Director of a Limited Company in a criminal act of corruption in a hospital development project (study of decision number 15 / Pid.Sus-TPK / 2018 / PN.Mdn)The legal research method used in this study is a type of normative legal research that is research used by searching or analyzing and analyzing library materials, one of which is Decision No. 15 / Pid.Sus-TPK / 2018 / PN.Mdn. Then based on the results of research on Decision No. 15 / Pid.Sus-TPK / 2018 / PN.Mdn it can be concluded that based on the deeds and errors of the Director of PT. Care Indonusa has fulfilled the element of error, criminal liability requirements and found no excuses for excuses or justifications, so that criminal liability can be requested from the Director of a Limited Liability Company. Based on the above, the judge sentenced him to 5 (five) years in prison as a form of criminal liability to the Director of PT. Care Indonusa.